High expression of lncRNA SNHG1 in prostate cancer patients and inhibition of SNHG1 suppresses cell proliferation and promotes apoptosis - Qi Tang; Zhen Li; Weijun Han; Shujie Cheng; Yi Wang (Wolters Kluwer Medknow Publications, 2020)
Objective: This study aimed to investigate the expression of long non-coding RNA (lncRNA) small nucleolar RNA host gene 1 (SNHG1) in prostate cancer (PCa) patients and to assess the effects of SNHG1 on PCa cell proliferation and apoptosis. Materials and Methods: A total of 134 PCa patients were randomly included from patients who underwent surgical resection at our hospital from October 2015 to December 2016. The SNHG1 expression levels in PCa tissues and paired adjacent non-cancerous tissues were detected by quantitative reverse transcription polymerase chain reaction (qRT-PCR). The association of the SNHG1 expression with clinical-pathological features of PCa patients was summarized and evaluated. A short interfering (si) RNA targeting SNHG1 and pcDNA3.1-SNHG1 were transfected into PC3 and DU145 PCa cell lines, and transfection efficiency was verified by qRT-PCR. Cell proliferation and apoptosis were assessed by methylthiazolyldiphenyl-tetrazolium bromide (MTT) and terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assays, respectively. Results: The SNHG1 expression was significantly upregulated in PCa tumor tissues compared with paired adjacent non-cancerous tissues. The SNHG1 expression was obviously associated with the TNM stage, Gleason Score, lymph node invasion, and long-term metastasis mortality rate. Silencing of SNHG1 inhibited cell proliferation and promoted apoptosis in PC3 and DU145 PCa cell lines in vitro, while overexpression of SNHG1 led to opposite results. Conclusion: LncRNA SNHG1 was upregulated and associated with aggressive malignant behavior in PCa progression. SNHG1 might serve as a potential prognostic biomarker and potential therapeutic target for PCa.